Didactic Anticipation of Two Matrix Multiplication Learning - Wati, Indah Kartika; Destiniar, Destiniar; Fuadiah, Nyiayu Fahriza (Universitas PGRI Madiun, 2020)
This study aims to create a didactic design in an effort to overcome the learning obstacle through DDR (Didactical Design Research) in learning multiplication of two matrices through prospective, meta-pedadidactic, and retrospective analysis stages. Data collection using the following techniques: 1) observation, namely observing learning activities, analyzing teaching materials and learning implementation plans used by teachers in classroom learning; 2) tests in the form of diagnostic tests for students to determine the learning obstacle, prerequisite ability tests, and final identification tests; 3) interviews with mathematics subject teachers by asking questions that lead to student difficulties and teacher difficulties in delivering mathematics learning material; and 4) instructional videos in the learning process. The data were analyzed to find a learning obstacle and based on these findings, a was prepared Hypothetical Learning Trajectory (HLT)which was outlined in a hypothetical didactic design. The didactic design that has been designed is implemented to test as well as validate HLT. The results of the instructional video recordings were analyzed in the meta-pedadactic stage. The didactic design of the two matrix multiplication material contains didactic anticipation that can be an alternative for the teacher when facing situations and responses that may occur.